Penyalahgunaan Keadaan Dalam Prosedur Permohonan Pailit Di Pengadilan Niaga - Ronald Saija (Faculty of Law, Universitas Pattimura, 2018)
In line with the rapidly growing trade trajectory, increasing and on an increasingly widespread and global scale, where corporate debt problem is getting complicated and requires effective legal regulation. The development of the global economy today requires the rule of bankruptcy law that is able to meet the legal needs of business people in the settlement of their accounts receivable. The monetary turmoil that occurred in mid-July 1997, resulted in a very wide impact on business development in Indonesia. In the face of this kind of thing, it is of course deemed necessary to take remedial measures, especially legal certainty in order to balance the interests of the company or the interest between creditors and debtors who go bankrupt. One of the legal means underlying the settlement of accounts payable is the regulations concerning the procedure of bankruptcy petition in the Commercial Court, as stipulated in Government Regulation in Lieu of Law No. 1 of 1998 on Amendment to the Law on Bankruptcy (Faillissement Verordening), which subsequently stipulated as Law No. 4 of 1998 on Bankruptcy, then underwent changes and improvements to Law of the Republic of Indonesia Number 37 Year 2004 concerning Bankruptcy and Suspension of Payment Obligation (PKPU). However, this law is felt to be less effective and less tested, due to the abuse of circumstances of interest, the factor of rights and power status factors in the current Bankruptcy application in the Commercial Court.